2011
DOI: 10.1253/circj.cj-11-0194
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Heat Shock Protein 70 Induces Cardiomyocyte Inflammation and Contractile Dysfunction via TLR2

Abstract: Background: Toll-like receptors (TLRs) are expressed on cardiomyocytes and recognize pathogen-associated molecular patterns. Whether endogenous molecules produced by tissue injury (damage associated molecular patterns, DAMPs) can induce cardiomyocyte inflammation via TLR signalling pathways and/or reduce cardiomyocyte contractility is unknown. Methods and Results:Primary cardiomyocytes isolated from nuclear factor κ B (NFκB)-luciferase knock-in mice were used to assess NFκB signalling. DAMPs, HSP60, HSP70 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 49 publications
3
64
0
1
Order By: Relevance
“…Furthermore, we found the distribution or migration of HSP70 from the cytoplasm to the extracellular matrix in the PSE-like muscle groups, as indicated in Figure 3. Previous study has shown that HSPs are located outside the cell, particularly after various pathological conditions such as inflammatory response syndrome, muscle contractile dysfunction and severe diseases (Mathur et al, 2011). Vega et al (2008) revealed that HSP70 translocates into membranes after stress and is released within membranous structures from intact HepG2 cells that activate the immune system to generate a systemic response to avoid the propagation of initial stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found the distribution or migration of HSP70 from the cytoplasm to the extracellular matrix in the PSE-like muscle groups, as indicated in Figure 3. Previous study has shown that HSPs are located outside the cell, particularly after various pathological conditions such as inflammatory response syndrome, muscle contractile dysfunction and severe diseases (Mathur et al, 2011). Vega et al (2008) revealed that HSP70 translocates into membranes after stress and is released within membranous structures from intact HepG2 cells that activate the immune system to generate a systemic response to avoid the propagation of initial stress.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 In general, these molecular chaperones are usually expressed intracellularly where they support the folding and the transport of a great variety of proteins. In contrast, membrane-bound and extracellular-located HSPs act as potent danger signals.…”
mentioning
confidence: 99%
“…The soleus and HSWG homogenates contained elevated levels of two known DAMPs (HSP60 and HSP72), suggesting that DAMPs released from specific skeletal muscle fibers may be capable of altering cardiac function. In support of this, eHSPs have been implicated as "alarm proteins" or "alarmins" (Manson et al 2012;Stoecklein et al 2012), and both HSP60 and HSP72 have been shown to interact with cardiac TLR4 and depress cardiomyocyte contractility (Kim et al 2009;Mathur et al 2011;Vabulas et al 2002). Therefore, the reduction in LVDP and +dP/dt observed in the hearts treated with soleus and HSWG muscle homogenates as well No significant differences were observed.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, when HSP60, an HSP normally confined to mitochondria, was added to cultured cardiomyocytes, cell shortening was reduced (Kim et al 2009). Similarly, when HSP72, the stressinducible isoform of the HSP70 family, was added to cultured cardiomyocytes, it was shown to cause an inflammatory response and decrease contractility (Mathur et al 2011). Thus, when skeletal muscle fibers are damaged and their contents released into the extracellular environment, specific molecules such as HSP60 and HSP72 may act as DAMPs and initiate an immune and/or inflammatory response in other cells and tissues, including the heart.…”
Section: Introductionmentioning
confidence: 99%